Using Human Development Indices to Identify Indicators to Monitor the Corona Virus Pandemic - Azza Abul-Fadl; Ayah Sarhan (Journal of Current Viruses and Treatment Methodologies, 2020)
Introduction The Corona virus (CoVID-19) pandemic has hit the most developed countries and has thence spread to inflict other countries around the world. It is the first pandemic that appears in countries not linked to poverty and poor hygiene. Aim To study the relationship between human development and the pattern of the pandemic caused by the CoVID-19 and to identify development indicators that can be useful in monitoring the pandemic. Methods Data collected included confirmed cases of CoVID-19 by country, number of cases that recovered and cases that died and population density per million in this particular country. The data for this information was obtained from the online data on the daily reports on CoVID-19 from the different countries. Data for the Human Development index (HDI) and the ranking for each country were obtained from the most recent United Nations Development of Populations (UNDP) report for 2019. We analyzed data for 166 countries for which the HDI was available for the date of cases reported online on 27th March, 2020 at midnight. Findings There were significant differences by ANOVA for the confirmed cases of CoVID19 cases and total cases per one million population between the countries in the 4 tier group of Human Development. HDI was significantly correlated with confirmed cases, case density and cases that died from CoVID-19 (P<0.01) for all countries but the significance decreased by tier group. Country ranking was inversely correlated with confirmed cases of CoVID-19 (r-0.25 at P=0.001), CoVID-19 cases per million (r-0.4 at P=0.000) and cases that died from CoVID-19 (r-0.2 at P=0.03). Recovery was not inked to HDI or country ranking. The upper HDI tier groups (very high, high and medium) showed significant correlations with total cases per one million population P<0.05, but no correlation was found with confirmed cases or cases that died or recovered from CoVID-19 P>0.05. Conclusions Total cases of CoVID-19 per one million population seems to be a better indicator of the pandemic. The pattern of spread is closely linked to industry.
Keywords: Corona virus